+0

# solve the problem using substitution.

0
315
2
+12

solve the problem using substitution.

x-2y=-2

3x-2y=2

Oct 25, 2017

#1
+7352
+2

This is a little bit different from the normal way of substituting, but it is still substution!

x - 2y  =  -2

3x - 2y  =  2

(x - 2y) - (3x - 2y)  =  (x - 2y) - (3x - 2y)

Since  x - 2y = -2 , we can substitute  -2  in for  x - 2y .

(x - 2y) - (3x - 2y)  =  (-2) - (3x - 2y)

Since  3x - 2y = 2 , we can substitute  2  in for  3x - 2y .

(x - 2y) - (3x - 2y)  =  (-2) - (2)

Distribute the  -1 .

x - 2y - 3x + 2y  =  -2 - 2

Combine like terms.

-2x  =  -4

Divide both sides by  -2 .

x  =  2

Now we know what  x  is. Let's plug this value into the first equation to find  y .

2 - 2y  =  -2

Subtract  2  from both sides.

-2y  =  -4

Divide both sides by  -2 .

y  =  2

Oct 25, 2017

#1
+7352
+2

This is a little bit different from the normal way of substituting, but it is still substution!

x - 2y  =  -2

3x - 2y  =  2

(x - 2y) - (3x - 2y)  =  (x - 2y) - (3x - 2y)

Since  x - 2y = -2 , we can substitute  -2  in for  x - 2y .

(x - 2y) - (3x - 2y)  =  (-2) - (3x - 2y)

Since  3x - 2y = 2 , we can substitute  2  in for  3x - 2y .

(x - 2y) - (3x - 2y)  =  (-2) - (2)

Distribute the  -1 .

x - 2y - 3x + 2y  =  -2 - 2

Combine like terms.

-2x  =  -4

Divide both sides by  -2 .

x  =  2

Now we know what  x  is. Let's plug this value into the first equation to find  y .

2 - 2y  =  -2

Subtract  2  from both sides.

-2y  =  -4

Divide both sides by  -2 .

y  =  2

hectictar Oct 25, 2017
#2
+12
0

solve the systems of equations:

3x+y=20
2x+3y=18     (no graph)

cesix  Oct 25, 2017